Pendaftaran Tanah - Nurasiah Harahap (Fakultas Hukum universitas Islam Sumatera Utara, 2021)
AbstractLegal counseling participants in Suka Beras Village, Perbaungan District, Serdang Bedagai Regency, North Sumatra Province generally do not understand the importance of land registration as regulated in Article 19 of Law Number 5 of 1960 concerning Basic Agrarian Principles, which is further regulated in a Government Regulation. Number 24 of 1997 concerning Land Registration, with the aim of: 1. to guarantee legal certainty and legal protection to holders of land rights, 2. to provide information to interested parties and, 3. to maintain an orderly land administration so that problems arise in the Suka Beras Village community that the land certificate is the responsibility of the Village Head for life, PPAT unilaterally makes land certificates used to the Bank where the community was previously not involved, suddenly cross disputes arise. Therefore, it is deemed necessary to carry out Community Service in the Village with the title